Suggestions for the improvement of the laws relating to Bankrupts - Kennedy, Alexander D. (Dublin Statistical Society, 1862)
The two suggestions I propose for the amendment of the Irish Bankruptcy Law. First ? That the Judge of the Bankrupt Court should be empowered to punish by imprisonment any bankrupt who may have committed any fraud or offence against the Bankruptcy Laws, or whose insolvency is attributable to rash speculation or unjustifiable extravagance, or who may have been guilty of any misconduct in relation to his trade. And secondly ? that every bankrupt who shall- pay less than 20s. in the pound, and who shall at any time subsequently acquire a certain sum of money or yearly income, shall from time to time be compellable to apply a portion of such money or income towards the payment of his debts due at the date of his bankruptcy, - until same be paid in full.
Read Monday, 18th November, 1861
Keywords: Irish Bankruptcy Law; Insolvency; 314.15